2002
DOI: 10.1093/chemse/27.1.81
|View full text |Cite
|
Sign up to set email alerts
|

Gustatory Projections from the Nucleus of the Solitary Tract to the Parabrachial Nuclei in the Hamster

Abstract: Taste-responsive cells in the nucleus of the solitary tract (NST) either project to the parabrachial nuclei (PbN) of the pons, through which taste information is transmitted to forebrain gustatory nuclei, or give rise to axons terminating locally within the medulla. Numerous anatomical studies clearly demonstrate a substantial projection from the rostral NST, where most taste-responsive cells are found, to the PbN. In contrast, previous electrophysiological studies in the rat have shown that only a small propo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

12
43
0

Year Published

2004
2004
2016
2016

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 62 publications
(55 citation statements)
references
References 49 publications
12
43
0
Order By: Relevance
“…From a technical perspective, although our local infusion studies targeted the mCeA, it is likely that the entire CeA was within the boundaries of drug/vehicle injections. Finally, we report here that the rNTS and LPB were also activated in response to sodium gratification; however, such a finding was expected given the known role of these structures in receiving and processing sodium taste information (42,43).…”
Section: Discussionmentioning
confidence: 66%
“…From a technical perspective, although our local infusion studies targeted the mCeA, it is likely that the entire CeA was within the boundaries of drug/vehicle injections. Finally, we report here that the rNTS and LPB were also activated in response to sodium gratification; however, such a finding was expected given the known role of these structures in receiving and processing sodium taste information (42,43).…”
Section: Discussionmentioning
confidence: 66%
“…An interspecies difference between rat and hamster has also been reported in the proportion of afferent projection of second-order gustatory relay neurons to the PbN. For instance, it was reported that 34.1% (53) or 45% (42) of the taste neurons in the NST project to the PbN in the rat, whereas a larger percentage (80.2%) was reported in an investigation with hamsters (7).…”
Section: Discussionmentioning
confidence: 98%
“…Gustatory information elicited from the tongue and oropharyngeal cavity is initially carried to the rostral portion of the nucleus of the solitary tract (NST) by the VIIth, IXth, and Xth cranial nerves, and these terminals are distributed in a topographic fashion with rostral-caudal sequence in the rostral NST (2,9,23,24,89). From the NST, ascending gustatory fibers project to third-order taste cells within the PbN of the pons (7,22,42,46,(53)(54)(55)87). Two separate routes carry taste information from the PbN further to the forebrain taste areas and cortex: the ventral forebrain pathway that involves the central nucleus of the amygdala (CeA), the lateral hypothalamus (LH), the bed nucleus of the stria terminalis (BNST), the substantia innominata (3,12,16,21,31,33,34,41,47,63,64,71); and the thalamocortical pathway that is characterized by the involvement of the bilateral VPMpc, which, in turn, carries taste information to the gustatory cortex (GC) (5,25,45,48,51).…”
mentioning
confidence: 99%
“…Electrophysiological experiments find that from about 35 to 80% of NST taste neurons are antridromically invaded by stimulation in the PBN (Cho et al 2002b;Monroe and DiLorenzo 1995;Ogawa and Kaisaku 1982;Ogawa et al 1984). Moreover, stimulating the CeA, LH, and GC influences taste responses in both the NST and PBN cells.…”
Section: Nst Versus Pbnmentioning
confidence: 99%